MODIFIKASI UKURAN PARTIKEL ENDOSPERMA BIJI MELINJO (Gnetum gnemon L.) DAN IDENTIFIKASI KANDUNGAN SENYAWA FITOKIMIA - Pratiwi, Eskarani Tri (BENZENA Pharmaceutical Scientific Journal, 2023)
Melinjo (Gnetum gnemon L.) is one of commodities growing throughout Indonesia. The seed of gnetum gnemon contains a group of stilbenoid bioactive compounds such as resveratrol and gnetin C which show antioxidant activity. This study aims to reduce the particle size and identify the active compounds contained in the endosperm of gnetum gnemon seeds. Formation of submicron gnetum gnemon seed powder by grinding using ball milling at 1000 rpm using 50 balls sized 9.22 mm for 120 minutes and measuring particle size using a particle size analyzer (PSA). Identification of the bioactive compound using phytochemical screening and then identification using the thin layer chromatography method with silica gel 60 F254 stationary phase and the mobile phases of chloroform, ethyl acetate, and formic acid (5:4:1), as well as the total phenol test using the Folin-Ciocalteu method. The resulting particle size obtained was 975.6 nm with a polydispersity index value of 0.453, identification of the bioactive compound content showed the presence of phenolic, flavonoids, saponins, and tannins, then identification using the thin layer chromatography (TLC) method showed the Rf gnetin c and resveratrol values respectively were 0.67 and 0.72 and the total phenol test results with a value of 4.319 ± 0.065 µg/mL. Based on these results the gnetum gnemon seed endosperm was reduced in size using the ball milling method and contained active compounds of the stilbenoid group. Keywords: gnetum gnemon, endosperm, resveratrol, gnetin c